Levetiracetam as an Alternative to Phenytoin for Prophylactic Use in Post-Traumatic Seizures: a Literature Review - Nagatri, Gabriela; Situmorang, Dicky Arjuna; Ramoti, Natanael; Siahaan, Andre Marolop Pangihutan; Indharty, Rr. Suzy; Tandean, Steven (Jurnal Neuroanestesi Indonesia, 2024)
Traumatic brain injury (TBI) is a common concern for the causes of disability and mortality and it can cause post-traumatic seizure (PTS). Currently, Brain Trauma Foundation (BTF) recommends phenytoin (PHY) as early PTS prophylaxis for patients with severe TBI. The two most common drugs prescribed for PTS are levetiracetam (LEV) and PHY. However, PHY displays a wide array of disadvantages. LEV appears as a better alternative to PHY because of its easier administration, the absence of need for drug level monitoring, lower drug-drug interaction, and better side-effects profile. It is due to the linear elimination kinetics LEV had in comparison to PHY that have zero order pharmacokinetics. Theoretically, LEV is better than PHY. But according to prior studies, LEV and PHY have comparable efficacy at preventing PTS in the early stages. Furthermore, the current evidence is insufficient to definitely recommend LEV over PHY in terms of effectiveness and adverse effects. This study aimed to analyze levetiracetam as an alternative to phenytoin for prophylactic use in post-traumatic seizure.